Pine Needle Energy Potential in Conifer Forest of Western Himalayan: DOI: 10.32526/ennrj.18.1.2020.06 - Sharma, Vishal; Kamal Sharma, Rajeev (Environment and Natural Resources Journal, 2019)
The present study estimates the energy potential of pine needles in the western Himalayan territory. Both a single point estimation approach and tree-canopy density approach were carried out to determine the net annual pine needle litterfall for different types of conifer forest. The annual net and gross pine needles yield in the year 2018 have been estimated to be 67.99 million tonnes and 59.02 million tonnes respectively. It provides an annual primary energy (APE) potential in electric and thermal energy form. The calculated thermal energy varied from 1.16-1.34 pJ which can provide a backup of 0.09-0.1 billion kWh. Thus, the pine needle offers a source of renewable fuel with excellent combustion characteristics of 18.64 MJ/kg. Additionally, the massive pine needles would result in a net increment of economic energy to the Himalayan regions and also control the threats of forest fires and, most importantly, scale-down the environmental pollution.